2005
DOI: 10.1038/sj.bjc.6602835
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin expression in a pancreatic cell line is modulated by a TNFα-dependent elastase

Abstract: Endostatin, an inhibitor of angiogenesis, is a 20 kDa fragment of the basement membrane protein, collagen XVIII. The formation of endostatin relies upon the action of proteases on collagen XVIII. TNFa, produced by activated macrophages, is a multifunctional proinflammatory cytokine with known effects on endothelial function. We postulated that TNFa may modulate the activities of proteases and thus regulate endostatin formation in pancreatic cells. Collagen XVIII/endostatin mRNA was expressed in one pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…25 The same authors have subsequently shown that collagen XVIII/endostatin mRNA is expressed in the SUIT-2 pancreatic cell line, and that endostatin is found in the cell-conditioned medium of these cells. 26 In a recent publication by Abollahi et al it has been shown that endostatin treatment of endothelial cells leads to a regulation of multiple genes in a cDNA array that potentially are involved in the angiogenic switch in vitro. Interestingly, the finding was validated in vivo in human pancreas samples including normal, inflamed and cancerous tissue.…”
mentioning
confidence: 98%
“…25 The same authors have subsequently shown that collagen XVIII/endostatin mRNA is expressed in the SUIT-2 pancreatic cell line, and that endostatin is found in the cell-conditioned medium of these cells. 26 In a recent publication by Abollahi et al it has been shown that endostatin treatment of endothelial cells leads to a regulation of multiple genes in a cDNA array that potentially are involved in the angiogenic switch in vitro. Interestingly, the finding was validated in vivo in human pancreas samples including normal, inflamed and cancerous tissue.…”
mentioning
confidence: 98%
“…This suggested that the inhibitory effects of VEGF and bFGF siRNA on endostatin secretion may occur following its transcription and translation, and that modulating protein secretion may be its main mechanism. Brammer et al (13) confirmed that collagen XVIII is expressed in pancreatic cancer cells, and can be released into the medium. Heljasvaara et al (14) showed that particular matrix metalloproteinases (MMPs) can degrade collagen XVIII and generate biological, suggesting that endostatin is hydrolysized from collagen XVIII.…”
Section: Discussionmentioning
confidence: 98%
“…Production of endostatin is dependent on the action of tumor infiltrating macrophages that secrete elastases, which in turn act on collagen XVIII, leading to the release of a bioactive protein fragment (40). Cytokines, such as the proinflammatory TNF-␣, interfere with the yield of endostatin production (41). It is still not clear whether all circulating endogenous endostatin is functional.…”
Section: Discussionmentioning
confidence: 99%